Froelich Gladstone Rainey (1907-92) - Bockstoce, John (ARCTIC, 1993)
Froelich Rainey, one of the central figures in the development of arctic archaeology, died on 11 October 1992. He was a leader in world archaeology and had made important discoveries on four continents during a career that spanned half a century; yet it was his early work, in Alaska, that he regarded as his most significant research.